Climate Variations in the Past 250 Million Years and Contributing Factors. Issue 2 (15th February 2023) - Li, Xiang; Hu, Yongyun; Yang, Jun; Wei, Mengyu; Guo, Jiaqi; Lan, Jiawenjing; Lin, Qifan; Yuan, Shuai; Zhang, Jian; Wei, Qiang; Liu, Yonggang; Nie, Ji; et al.
Abstract: We simulate climate variations in the past 250 million years (Myr), using the fully coupled Community Earth System Model version 1.2.2 (CESM1.2.2) with the Community Atmosphere Model version 4 (CAM4). Three groups of simulations are performed, each including 26 simulations, with a 10‐million‐year interval. The Control group is constrained by paleogeography, increasing solar radiation, and reconstructed global mean surface temperatures (GMSTs) by tuning CO2 concentrations. No ice sheets are prescribed for all simulations except for the pre‐industrial (PI) simulation in which modern geography, ice sheets and vegetation are used. Simulated zonal mean surface temperatures are always higher than those of proxy reconstructions in the tropics, but lower than those of proxy reconstructions at middle latitudes. The relative importance of individual contributing factors for surface temperature variations in the past 250 Myr is diagnosed, using the energy‐balance analysis. Results show that greenhouse gases are the major driver in regulating GMST variations, with a maximum contribution of 12.2°C. Varying surface albedo contributes to GMST variations by 3.3°C. Increasing solar radiation leads to GMST increases by 1.5°C. Cloud radiative effects have relatively weak impacts on GMST variations, less than ±0.8°C. For comparison, two groups of sensitivity simulations are performed. One group has the CO2 concentration fixed at 10 times the PI value, and the other group has fixed CO2 concentration of 10 times the PI value and fixed solar radiation at the present‐day value, showing that varying both paleogeography and solar constant and varying paleogeography alone result in GMST changes by 7.3°C and 5.6°C, respectively. Plain Language Summary: The climate system has experienced drastic changes in the past 250 million years (Myr). A warm climate state was associated with the Pangea supercontinent (∼250 to 200 million years ago [Ma]). Climate became cooler in the middle and late Jurassic (∼174–145 Ma) during the breakup of the supercontinent. It warmed again in the late Cretaceous (∼100–66 Ma) and started cooling in the early Eocene (∼56 Ma) when fragmented continental plates reassembled. In the present study, we simulate climate variations in the past 250 Myr, using a fully coupled atmosphere‐ocean climate model. Three groups of simulations are performed, and each group includes 26 snapshot simulations, with a time interval of 10 million years. The simulation results demonstrate that greenhouse gases are the major driver in regulating global mean surface temperature (GMST) variations, and varying paleogeography also has important impacts on GMST variations through the surface albedo effect. In addition, cloud fraction and its radiative effects vary over different paleogeography and warm‐cool climate states. Key Points: Climate evolution in the past 250 million years is simulated using the fully coupled climate model CESM1.2.2 (CAM4) every 10 million years Greenhouse gases are the major factor in regulating surface temperature variations in the past 250 million years Changes of continental configurations have significant contributions to surface temperature variations over tectonic timescales